"TRANSIENT ABSORPTION OF GOLD NANOPARTICLES OF VARIOUS DIAMETERS " - Ibrayev, N.Kh.; Seliverstova, E.V.; Kanapina, A.E. (Eurasian Physical Technical Journal, 2022)
The transient absorption of gold nanoparticles with an average diameter of 13±5 and 48±16 nm upon photoexcitation by nanosecond laser pulses has been studied. It was shown that the maximum of stationary absorption exhibits as a wide structureless band with a maximum at about 520–540 nm. The transient absorption band of gold nanoparticles with a maximum at about 430 nm has a fine structure with a frequency of maxima of 6–8 nm and it does not depend on the size of the nanoparticles. The absorption duration decreases with a decrease in the average size of nanoparticles. The lifetime of transient absorption is equal to 23±2 and 19.5±2 ns for large and small particles, respectively. The nanosecond lifetime of the transient absorption of Au nanoparticles is the result of a prolonged relaxation process in the “interface of Au nanoparticle–solvent molecule” system as a manifestation of hindered heat exchange with the environment.